Pseudotumoral neuroparacoccidioidomycosis of the posterior fossa: A case report and review of the literature - Jorge, Luiz; Yamashita, Seizo; Trindade, André; Lima Resende, Luiz; Zanini, Marco; Caldeira Xavier, José; De Toledo Moraes, Marcelo (Scientific Scholar, 2017)
Background: Paracoccidioidomycosis is a systemic mycosis of significant importance in some Latin American countries. The widespread use of neuroimaging methods has shown that involvement of the central nervous system was more frequent than previously reported. The most common form of occurrence of neuroparacoccidioidomycosis is the pseudotumoral one. The authors report a case of pseudotumoral neuroparacoccidioidomycosis localized in the posterior fossa. Case Description: A 49-year-old single man, rural worker, born and raised in Laranjal Paulista-SP, was admitted to the hospital with 3 months history of bilateral occipital headache every day. Along with a history of active smoking and previous use of alcohol, the patient reported personal history of mild occipitotemporal injury 3 months ago. The patient was submitted to computed tomography in a 16-row multidetector scanner, which revealed a nodular hypodense lesion with a ring-enhancement and associated perilesional edema in the left cerebellar hemisphere. Radiological workup was initiated to investigate the eventual primary neoplastic site. Conclusion: The analysis of the lipid peak by spectroscopy of proton magnetic resonance may indicate the neurological involvement by paracoccidioidomycosis, notably in patients with concomitant risk and pulmonary involvement signals.
Keywords: Central nervous system; Computed tomography; Magnetic resonance spectroscopy; Neuroparacoccidioidomycosis; Paracoccidioidomycosis